The climate and the economy - Johannes Breckenfelder; Bartosz Maćkowiak; David Marqués Ibá\~nez; Conny Olovsson; Alexander Popov; Davide Porcellacchia; Glenn Schepens (European Central Bank (ECB), 2023)
Climate change and the public policies to arrest it are and will continue reshaping the global economy. This Discussion Paper draws on economic research to identify some key medium- and long-run economic implications of these developments. It explores implications for growth, innovation, inflation, financial markets, fiscal policy, and several socio-economic outcomes. The main message that emerges is that climate change will cause income divergence across individuals, sectors, and regions, adjustment in energy markets, increased inflation variability, financial markets stress, intensified innovation, increased migration, and rising public debt. These challenges appear manageable for EU member states, especially under an early and orderly transition scenario. At the same time, the direction, scope, and speed of economic transformation is subject to large uncertainty due to two separate factors: the wide range of climate scenarios for a given trajectory of greenhouse gas emissions and the exact policy path governments choose, especially in the context of the ongoing Russian aggression in Ukraine.
Keywords: D6; E3; F2; G2; O1; Q5; 330; Climate change; growth; inflation; financial markets; socio-economic implications